A MODEL OF SUSTAINABLE ENVIRONMENTAL ADMINISTRATION DEVELOPMENT BASED ON SAPPAYA DHAMMA PRIMARY SCHOOLS UNDER BANGKOK METROPOLITAN ADMINISTRATION - Guttavamso (Sukprasert), Phra Meesak; Chamnisast, Booncherd; Boonpoo, Somsak (Journal of Educational Review Faculty of Education in MCU, 2020)
The objective of this research paper was to propose a model of sustainable environmental administration development based on Sappaya Dhamma for primary schools under Bangkok Metropolitan Administration. Mixed methods research was conducted and three steps were designed. Step 1: Study of environmental management conditions in primary schools under Bangkok Metropolitan Administration. The questionnaire was used for collecting 390 administrators and teachers. Data were analyzed by descriptive statistics consisted of frequency, percentage, mean and standard deviation. Step 2: the model was developed by interviewing 24 key informants, and the data was analyzed by content analysis. Step 3: proposing a model by focus group discussion with 9 experts using focus group discussion guidelines, and data was analyzed by content analysis. The results of the research were found that 1) a model of sustainable environmental administration development based on Sappaya Dhamma for primary schools under Bangkok Metropolitan Administration consisted of 4 elements: 1) Principle, 2) Purpose, 3) Method of Action, and 4) Process. The environmental management in primary schools covered all 3 aspects which were (1) the social environment within the school that arranged the environment of material, buildings and educational institutions, (2) social environment within the school which were policies, planning, supervision, evaluation of culture, traditions, rules and regulations related to environment in educational institutions, and (3) teaching and learning management that was the management of learning, creativity, development activities and reporting of performance to support environmental performance by developing environmental management in accordance with sustainable Sappaya Dhamma which was suitable thing that supports helping the administration to be effective, including (1) suitable residences, (2) appropriate travel, (3) proper communication, (4) suitable person, (5) appropriate food, (6) appropriate weather, and (7) appropriate performance.